Uncle Jeds barbershop - Mitchell, Margaree King (Hongkong : Aladdin, 1993)
Despite serious obstacles and setbacks Sarah jeans uncle Jed, the only black barber in the country, pursues his dream of saving enough money to open his own barbershop.
Keywords: Uncle's - fiction; Barber's - fiction